The role of Gestational Diabetes Mellitus and pelvic floor 3D-ultrasound assessment during pregnancy predicting urinary incontinence: a prospective cohort study - Sartorao Filho, Carlos Izaias [UNESP] (2023)
Postpartum urinary incontinence may have a severe impact on women’s health. Despite pregnancy and parturition being the most recognized risk factors, methods to identify new pregnant predictor risk factors are needed. Our study investigated the Gestational Diabetes Mellitus, clinical and pelvic floor 3D-ultrasound markers in pregnant women as predictors for 6–18 months of urinary incontinence. This prospective cohort study included nulliparous pregnant women submitted to Gestational Diabetes Mellitus screening in the second trimester. Pelvic floor 3D Ultrasound was performed at the second and third trimesters of gestation to evaluate the pelvic floor muscles and functions. Clinical data, the ICIQ-SF, and ISI questionnaires for urinary incontinence were applied in the third trimester and 6–18 months postpartum. Univariate analysis (P <.20) to extract risk factors variables and multivariate logistic regression analysis (P <.05) to obtain the adjusted relative ratio for urinary incontinence were performed. A total of 93 participants concluded the follow-up. Using the variables obtained by univariate analysis and after adjustments for potential confounders, multivariate analysis revealed that Gestational Diabetes Mellitus exposure was a solid and independent risk factor for 6–18 months of urinary incontinence (Adjusted RR 8.08; 95%CI 1.17–55.87; P:0.034). In addition, a higher Hiatal area observed in distension maneuver from the second to third trimester was negatively associated (Adjusted RR 0.96; 95%CI 0.93–0.99; P:0.023). In conclusion, Gestational Diabetes Mellitus was positively associated with 6–18 months of urinary incontinence, and higher Hiatal area distension was negatively associated.